The Language Institute Mahachulalongkornrajavidyalaya University : Policy, Mission, Vision, Strategy and Future Goals - Nathabamrung, phramaha santi (Mahachula Academic Journal, 2025)
Academic articles to study the future goals of the Language Institute, Mahachulalongkornrajavidyalaya University, should be related to the important role of promoting education, disseminating language and developing language skills for students and the general public, including supporting knowledge of Buddhism and Thai culture to the international arena. The main goals include: 1. Develop linguistic knowledge to support the study of Buddhism, promoting the teaching of related languages ​​such as English, Pali, etc. 2. Be a center for language study and Dhamma translation, focusing on creating translators with expertise in Buddhism to support the translation of scriptures and religious documents into various languages. 3. Support the spread of Buddhism at the international level, organizing training and building networks with international organizations. 4. Enhance language research potential, develop research on language and language teaching to create new knowledge beneficial to teaching and learning. 5. Use educational technology and innovation to develop online teaching platforms and employ AI or other new technologies to reach learners both domestically and internationally. 6. Support academic cooperation, establishing partnerships with universities or international educational institutions to expand opportunities for linguistic and cultural knowledge exchange.